The misregulation of mitochondria-associated genes caused by GAGA-factor lack promotes autophagic germ cell death in Drosophila testes. - Dorogova, N.V.; Fedorova, S.A.; Bolobolova, E.U.; Baricheva, E.M. (Genetica, 2023)
The Drosophila GAGA-factor encoded by the Trithorax-like (Trl) gene is DNA-binding protein with unusually wide range of applications in diverse cell contexts. In Drosophila spermatogenesis, reduced GAGA expression caused by Trl mutations induces mass autophagy leading to germ cell death. In this work, we investigated the contribution of mitochondrial abnormalities to autophagic germ cell death in Trl gene mutants. Using a cytological approach, in combination with an analysis of high-throughput RNA sequencing (RNA-seq) data, we demonstrated that the GAGA deficiency led to considerable defects in mitochondrial ultrastructure, by causing misregulation of GAGA target genes encoding essential components of mitochondrial molecular machinery. Mitochondrial anomalies induced excessive production of reactive oxygen species and their release into the cytoplasm, thereby provoking oxidative stress. Changes in transcription levels of some GAGA-independent genes in the Trl mutants indicated that testis cells experience ATP deficiency and metabolic aberrations, that may trigger extensive autophagy progressing to cell death.